Peculiarities of enterprise equity and equity accounting - Vaičiulytė, Ieva; Rudžionienė, Kristina (Buhalterinės apskaitos teorija ir praktika, 2014)
From the fundamental accounting equation becomes the evidence that equity is one of the most significant indicator of enterprise state. So the process of enterprise equity formation that should be not only legally based but also economically reasoned is definitely relevant aspect in accounting. Both the reform of public sector and complex and hard to prognosticate conditions in private sector also laws of free market that promote to respond operative to external factors require complex and comprehensive equity accounting researches. The aim of this article – compare peculiarities of different enterprise equity accounting (closed share holding company, state enterprise, state budget institution). Tasks that have been set to reach the aim: 1) scrutinize requirements for share holding company, state enterprise, state budget institution of their equity accounting; 2) compare their peculiarities of equity accounting: structure of equity, similarities and differences between 3rd class of a chart of accounts. After the research becomes the evidence that equity accounting of closed share holding company is strictly regulated by laws and standards while equity accounting of state enterprise and budget institution is almost unregulated. The most specific structure of equity is in state budget institution. Whereas the structure of equity in state enterprise is closer to the structure of equity in closed share holding company. Consequently in a number of cases requirements for state enterprise of their equity accounting might become closer to requirements for closed share holding company, for example, requirements for shareholders equity, formation of reserves. In this way the stringency of regulation for closed share holding company would be taken to regulate state enterprise equity accounting. However, closed share hold company has specificities that might not be adjusted in state enterprise, for example, requirements for share premium, reserve for own shares because the activity of state enterprise is not intended to reach for profit. After the comparison of the 3rd class of a chart of accounts becomes the evidence that closed share holding company and state enterprise have many similarities. However, closed share holding company has far and away more sub accounts to register equity and changes of equity.